2016
DOI: 10.1007/s13205-016-0423-9
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of mixed infection of Beijing/Non-Beijing strains among multi-drug resistant Mycobacterium tuberculosis in Pakistan

Abstract: Tuberculosis (TB) remains as one of the deadliest diseases after HIV globally with 95 % of deaths confined to low-and-middle income countries. Pakistan is fifth among the 22 high-burden TB countries with the incidence rate of 230/100,000 persons, however, studies related to prevalent Mycobacterium tuberculosis strains and their spread, drug resistance pattern and evolutionary genetics are inadequate. The present study was undertaken to highlight the circulation of M. tuberculosis strains causing drug resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Of these, 22 patients were already known DM and due to taking medicine they had fasting blood sugar level <126 mg/dl at the time of data collection. The results of present study are similar to those of Amin et al that reported co-occurrence of TB and DM in 14% patients of Peshawar, Pakistan 6 . Similarly, another study of Pakistani population conducted by Jabbar et al in 2006 showed co-occurrence of TB and DM among 11.9% study participants 18 .…”
Section: Fig1 Overall Prevalence Of Diabetes Among Tb Patientssupporting
confidence: 92%
See 1 more Smart Citation
“…Of these, 22 patients were already known DM and due to taking medicine they had fasting blood sugar level <126 mg/dl at the time of data collection. The results of present study are similar to those of Amin et al that reported co-occurrence of TB and DM in 14% patients of Peshawar, Pakistan 6 . Similarly, another study of Pakistani population conducted by Jabbar et al in 2006 showed co-occurrence of TB and DM among 11.9% study participants 18 .…”
Section: Fig1 Overall Prevalence Of Diabetes Among Tb Patientssupporting
confidence: 92%
“…4 Therefore, it is essential to study the prevalence of both diseases in order to understand the factors associated with their co -occurrance. TB countries 6 . The World Health Organization (WHO) reported an estimated incindence of 275 cases per 100,000 persons and prevalence of 342 cases per 100,000 population 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiplex PCR method was used to distinguish Beijing and non-Beijing genotypes as previously described 17 that region spanning genes Rv2816 to Rv2819 including part of Rv2820 is missing in Beijing genotype of M. tuberculosis strain. A set of primers BJ-F: 5ʹ-ACCGAGCTGATCAAACCCG -3ʹ and BJ-R: 5ʹ-ATGGCACGGCCGACCTGAATGAACC -3ʹ amplified the 239 bp PCR product containing regionspecific part of Rv2819 and part of Rv2820 in Beijing genotypes.…”
Section: Detection Of Beijing and Non-beijing Genotypesmentioning
confidence: 99%
“…Furthermore, AMK, KAN and CAP resistance has been associated with mutations in the 16S rRNA gene ( rrs ), between nucleotide positions 1400 and 1500 particularly mutations in positions 1401, 1402 and 1484; up to 87% of KAN and AMK resistance worldwide is attributed to these mutations (especially a1401g) [11, 12]. Additionally, KAN and CAP resistance can also be mediated by mutations in the eis and tlyA genes, respectively.It is now well-documented that the frequencies of drug resistance conferring mutations described above vary between M. tuberculosis geno-groups and geographically [13, 14], which pose a significant challenge in the development of sequence-based diagnostic tools and their applicability without a thorough evaluation of their performance with respect to setting. Case in point is the MTBDR sl test which, although it is generally useful in detecting resistance to second-line anti-TB drugs, it has varying sensitivity especially in detecting FQ resistance [15].…”
Section: Introductionmentioning
confidence: 99%